Transplantation of Human Glial Progenitors to Immunodeficient Neonatal Mice with Amyotrophic Lateral Sclerosis (SOD1/rag2) - Luiza Stanaszek; Piotr Rogujski; Katarzyna Drela; Michal Fiedorowicz; Piotr Walczak; Barbara Lukomska; Miroslaw Janowski (MDPI AG, 2022)
Amyotrophic lateral sclerosis (ALS) is a progressive, fatal disease with no effective therapy. The neurodegenerative character of ALS was an appealing target for stem cell-based regenerative approaches. Different types of stem cells have been transplanted in both preclinical and clinical settings, but no convincing outcomes have been noted. Human glial restricted precursors (hGRPs) transplanted intraventricularly to neonatal, immunodeficient mice rescued lifespan of dysmyelinated mice. Intraspinal injection of hGRPs also provided benefits in the mouse model of ALS. Therefore, we have recently developed an immunodeficient model of ALS (double mutant SOD1/rag2), and, in this study, we tested the strategy previously used in dysmyelinated mice of intraventricular transplantation of hGRPs to immunodeficient mice. To maximize potential therapeutic benefits, the cells were implanted into neonates. We used magnetic resonance imaging to investigate the progression of neurodegeneration and therapeutic responses. A cohort of animals was devoted to survival assessment. Postmortem analysis included immunohistochemistry, Nissl staining, and Western blots. Cell transplantation was not associated with improved animal survival, slowing neurodegeneration, or accumulation of misfolded superoxide dismutase 1. Postmortem analysis did not reveal any surviving hGRPs. Grafting into neonatal immunodeficient recipients did not prevent ALS-induced cell loss, which might explain the lack of positive therapeutic effects. The results of this study are in line with the modest effects of clinical neurotransplantations. Therefore, we urge stem cell and ALS communities to develop and implement cell tracking methods to better understand cell fates in the clinic.